Modal Intelektual dan Dampaknya bagi Keberhasilan Organisasi - T. Elisabeth Cintya Santosa; Rony Setiawan (Universitas Kristen Maranatha, 2007)
Business world and economics have been knocked over by a waving drastic change. With new era appearance, information era, hence happened friction